Combined activation of MAP kinase pathway and β-catenin signaling cause deep penetrating nevi - Yeh, Iwei (Nat Commun, 2017)
Deep penetrating nevus (DPN) is characterized by enlarged, pigmented melanocytes that extend through the dermis. DPN can be difficult to distinguish from melanoma but rarely displays aggressive biological behavior. Here, we identify a combination of mutations of the β-catenin and mitogen-activated protein kinase pathways as characteristic of DPN. Mutations of the β-catenin pathway change the phenotype of a common nevus with BRAF mutation into that of DPN, with increased pigmentation, cell volume and nuclear cyclin D1 levels. Our results suggest that constitutive β-catenin pathway activation promotes tumorigenesis by overriding dependencies on the microenvironment that constrain proliferation of common nevi. In melanoma that arose from DPN we find additional oncogenic alterations. We identify DPN as an intermediate stage in the step-wise progression from nevus to melanoma. In summary, we delineate specific genetic alterations and their sequential order, information that can assist in the diagnostic classification and grading of these distinctive neoplasms.